Futsal Field Promotion System Using Augmented Reality Method (Case Study: Segodo Tarik Futsal Field): Sistem Promosi Lapangan Futsal Menggunakan Metode Augmented Reality (Studi Kasus: Lapangan Futsal Segodo Tarik) - Alim, Kholqi; Eviyanti, Ade; Findawati, Yulian; Rosid, Mochamad Alfan (Universitas Muhammadiyah Sidoarjo, 2023)
Futsal is a multi-sprint sport with a high-intensity phase. In addition, the game of futsal is very dependent on the technical abilities of each player. To implement trained and conceptualized tactics and strategies, individual techniques are combined. To play futsal properly, you must learn some basic techniques and practice them often. Various technologies have been developed in the field of sports to improve player performance, including the development of an Arduino-based futsal ball throwing device. Augmented reality (AR) is the process of generating additional information about existing objects by rendering them in real time directly or indirectly from physical objects by adding objects to the virtual world. Based on the research that has been done under the title